The Concept of Poverty, its Measurement and Tendencies in Lithuania - Šileika, Algis; Zabarauskaitė, Rasa (Ekonomika, 2006)
Poverty is one of the most essential problems that most countries face over the world. Lithuania joined the implementation of Millennium Development Goals, which were adopted in 2000 by all the world’s Governments with the aim to reduce the proportion of people living in poverty. It was anticipated to reduce the poverty level from 16% to 13% by 2005 in Lithuania. But according to the data of Statistics Lithuania, the poverty level in Lithuania increased from 15.9% in 2003 to 16.9% in 2005. The solution of this problem demands a purposeful policy of the Government as well as the endeavor of people themselves. One of the first tasks to be performed when implementing poverty reduction measures in the country is the evaluation of poverty prevalence and the estimation of the number of the poor. The indicators chosen for poverty measurement highly influence the results of poverty research. Thus, indicators adjusted to the peculiarities of the country and based on its living standard should be used when the measuring poverty level. The article analyses the definition of poverty as well as its development since the 18th century. The key indicators for measuring poverty (relative poverty line, absolute poverty line, subjective poverty line, poverty gap, etc.) and their main limitations are discussed in the article. Poverty dynamics and income differentiation indicators in Lithuania are analysed in the second part of the article. The authors suggest that poverty measurement based on the relative poverty line is not effective in Lithuania, because it doesn’t show the real situation of poverty in the country. According to the relative poverty concept, people are considered to be living in poverty if their standard of living is substantially less than the general standard of living in society (ie. 50% of average consumption expenditure in Lithuania). Relative poverty measures are usually used in highly developed countries where more emphasis is put on satisfying intellectual and social rather than physical needs. It is argued that the absolute poverty line should be used in underdeveloped countries (in Lithuania as well) when calculating the poverty level Absolute poverty measured by the official poverty line representing the annual income required to allow a family of a given size to purchase the range of goods and services that are seen as constituting the minimum acceptable way of life in the country. According to the authors, the main causes of increased poverty in the last period in Lithuania were a too heavy tax burden for employees (which exceeded the average level of taxes in 15 ES countries) as well as a high differentiation of income.